A longitudinal investigation of older adults' physical activity: Testing an integrated dual-process model. Issue 2 (1st February 2017) - Arnautovska, Urska; Fleig, Lena; O'Callaghan, Frances; Hamilton, Kyra
Abstract : Objective: To assess the effects of conscious and non-conscious processes for prediction of older adults' physical activity (PA), we tested a dual-process model that integrated motivational (behavioural intention) and volitional (action planning and coping planning) processes with non-conscious, automatic processes (habit). Method: Participants ( N  = 215) comprised community-dwelling older adults ( M  = 73.8 years). A longitudinal design was adopted to investigate direct and indirect effects of intentions, habit strength (Time 1), and action planning and coping planning (Time 2) on PA behaviour (Time 3). Structural equation modelling was used to evaluate the model. Results: The model provided a good fit to the data, accounting for 44% of the variance in PA behaviour at Time 3. PA was predicted by intentions, action planning, and habit strength, with action planning mediating the intention-behaviour relationship. An effect of sex was also found where males used fewer planning strategies and engaged in more PA than females. Conclusions : By investigating an integration of conscious and non-conscious processes, this study provides a novel understanding of older adults' PA. Interventions aiming to promote PA behaviour of older adults should target the combination of psychological processes.